Gestão do conhecimento no Instituto Federal de Educação, Ciência e Tecnologia de Brasília (IFB): um diagnóstico pelo método Organizational Knowledge Assessment (OKA) - Amarante, Nadja Pessoa do (2015)
In current knowledge society, the intensive use and proper management of intellectual capital and of intangible assets are been regarded as basic conditions for the success of organizations, both private and public, in that it proved as generators of value and wealth more important than capital and labor. In this scenario, the Knowledge management arises as a method to mobilize the organizational knowledge in order to achieve the strategic goals and to increase the business intelligence to respond to the environment with innovation and expertise, through the use of methodologies and specific technologies. In the public sector, by means of knowledge management, we seek the improvement of efficiency, effectiveness, responsiveness and quality of policies and public services provided to citizens and society. However, the implementation of Knowledge Management in an organization requires, firstly, the adoption of a process of measuring and evaluating their performance in an appropriate and systematic use of knowledge assets, identifying potentialities as well as gaps and areas for improvement, whose data and information can serve as a basis for building a strategic plan for knowledge management. In view of this, the objective of this study was to diagnose the current level of preparation in knowledge management of the Federal Institute of Education, Science and Technology of Brasília (IFB), higher, basic and professional education institution under the Ministry of Education. The research consisted of a case study of descriptive and exploratory approach, and had as target population IFB managers of high and middle management, selected from intentional criteria such as length of time enrolled in the institution and exercise of management position. Data collection and analysis of the results were based on the system of quantification and methodological procedures from the Organizational Knowledge Assessment Method (OKA), developed by the World Bank, with the purpose of evaluating the ability of organizations to mobilize information and knowledge in order to achieve their strategic objectives and add value to products and services, through people, processes and systems. Considering the reviewed literature and the final results of this study, it was concluded that the IFB has average performance in managing the processes of creation, capture, storage, transfer and application of knowledge, due to the short time of its inception, the installed organizational culture and the lack of formalization of a knowledge management program until the present date.